Application of big data in historical science - Khymytsia, Nataliia; Ustyianovych, Taras (Видавництво Львівської політехніки, 2017)
The importance of the research is that it presents the usage of Big Data and history. The prospects and the main directions of the usage of the Big Data in historical science were analysed.
Keywords: history; historiography; techniques; Big Data; computing; the Internet